2022
DOI: 10.21873/invivo.12800
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Lymph Node Swelling Mimicking Breast Cancer Metastasis After COVID-19 Vaccination: A Japanese Case Report and Literature Review

Abstract: Background/Aim: COVID-19 started to spread as a pandemic in December 2019 and COVID-19 vaccination has been initiated worldwide. The efficacy of vaccination has been scientifically proven, but it might cause axillary lymph node swelling. To diagnose patients with axillary lymph node swelling caused by COVID-19 vaccination, we herein reviewed existing literature on this symptom. Case Report: We report the case of a 70-year-old woman with a breast tumour. She had undergone cecum cancer surgery and regular comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In our case, although there seemed to be no axillary lymph node swelling after the second vaccination (imaging was conducted 2 months after the second vaccination), swelling was observed after the third. We previously reported axillary lymph node swelling as a sideeffect of the first or second COVID-19 vaccination (19); therefore, this side-effect observed after the third vaccination can be considered similar to that after the first or second COVID-19 vaccinations.…”
Section: Discussionmentioning
confidence: 65%
“…In our case, although there seemed to be no axillary lymph node swelling after the second vaccination (imaging was conducted 2 months after the second vaccination), swelling was observed after the third. We previously reported axillary lymph node swelling as a sideeffect of the first or second COVID-19 vaccination (19); therefore, this side-effect observed after the third vaccination can be considered similar to that after the first or second COVID-19 vaccinations.…”
Section: Discussionmentioning
confidence: 65%
“…Breast radiologists are increasingly seeing patients with axillary adenopathy related to COVID-19 vaccination. COVID-19 vaccination can cause levels I–III axillary as well as cervical lymphadenopathy [ 16 , 17 ]. Au et al reported that a patient with colorectal cancer who had been receiving long-term PD-1 therapy experienced severe side effects related to immunotherapy after receiving the BNT16262 vaccine developed by Pfizer/BioNTech [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our research, surgical excision or CNB of C19-LAP-or SLDI-enlarged lymph nodes have been performed in 55 cases. 20,22,23,35,39,[41][42][43]47,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The histological diagnoses were as follows: negative for neoplasia, reactive hyperplasia, and florid reactive hyperplasia (39 cases), 23,39,[50][51][52][53][54][55][56][57][58][59][60][61] progressive transformation of germinal centres (1 case), 54 atypical follicular hyperplasia with light chain-restricted germinal centres (1 case) 62 granulomatous reaction (2 cases), 50,63 metastases (4 cases), 20,22,50 Kikuchi-Fujimoto disease (KFD; 6 cases), [40][41]…”
Section: Covid-19 Vaccines and Lymphadenopathymentioning
confidence: 99%
“…The present study is a pooled review based on 14 report s [20][21][22][35][36][37][38][44][45][46][47]52,72 and one unpublished case observed by the authors. In total, 26 cases are reported, including 17 (65%) female patients, 8 (32%) male patients, and one patient whose gender was not reported, 21 with an age range of 27-70 years.…”
Section: Fine Needle Aspiration Cytology In Cases Of Sldi and C19-lapmentioning
confidence: 99%
See 1 more Smart Citation